2009
DOI: 10.1016/j.jmb.2008.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Design and Signaling Mechanism of Light-Regulated Histidine Kinases

Abstract: Signal transduction proteins are organized into sensor (input) domains that perceive a signal and, in response, regulate the biological activity of effector (output) domains. We reprogrammed the input signal specificity of a normally oxygen-sensitive, light-inert histidine kinase by replacing its chemosensor domain by a light-oxygen-voltage (LOV) photosensor domain. Illumination of the resultant fusion kinase YF1 reduced net kinase activity by ~1000-fold in vitro. YF1 also controls gene expression in a light-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
351
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 323 publications
(381 citation statements)
references
References 50 publications
13
351
2
Order By: Relevance
“…We speculate that in the kinase-to-phosphatase transition, the connections of the PAS cores with their flanking C-terminal ␣-helices break. The highly conserved Asp residue of the "DIT" motif, which frequently terminates PAS core domains, mediates interactions of the core with these helices (22,(39)(40)(41). In BvgS, replacement of this Asp 695 residue with Ala abolished kinase activity, a finding consistent with this scenario (28).…”
Section: Mechanical Signal Transmission By Bvgs Linkermentioning
confidence: 59%
See 1 more Smart Citation
“…We speculate that in the kinase-to-phosphatase transition, the connections of the PAS cores with their flanking C-terminal ␣-helices break. The highly conserved Asp residue of the "DIT" motif, which frequently terminates PAS core domains, mediates interactions of the core with these helices (22,(39)(40)(41). In BvgS, replacement of this Asp 695 residue with Ala abolished kinase activity, a finding consistent with this scenario (28).…”
Section: Mechanical Signal Transmission By Bvgs Linkermentioning
confidence: 59%
“…Signal transduction between the perception and the enzymatic domains of sensor kinases generally involves combinations of rotation, scissor, or piston movements of coiled-coil regions (40)(41)(42)(43)(44)(45)(46)(47)(48)(49). A simple model is that a sensor kinase populates two thermodynamically stable structural states.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, many histidine kinases that have a PAS domain as signal input domain, show conservation of the connecting region between the PAS domain and the J␣-helix (47). This conserved sequence signature ( 125 DIT 127 ) is also present in YtvA (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…Interdomain Signal Transmission in YtvA-A recent study of engineered hybrid proteins, composed of the LOV domain of YtvA and the histidine kinase domain of FixL and connected via J␣-type helices of different lengths, has revealed that signals are transmitted from the sensory LOV domain to the histidine kinase domain via a 40 -60 o rotational movement within the ␣-helical coiled-coil linker (47). Therefore, these hybrid proteins act as light-triggered rotary switches (7,47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation